Evaluasi Prosedur Waktu Pengembalian Dokumen Rekam Medis Rawat Inap Di Rumah Sakit Umum X Surabaya - Indah Susilowati; Deni Luvi Jayanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Management of medical record documents must be monitored, both the time of their provision and the timeliness of their return. The establishment of standard operating procedures (SOP) at General Hospital X Surabaya aims to maintain administrative order and improve service quality. This includes the return of medical record documents, which the standard is 2x24 hours after the patient is declared home. However, there are still discrepancies in the implementation of the time for returning inpatient medical record documents to the storage room. The purpose was to determine the suitability of the procedure for returning inpatient medical record documents in the fourth quarter of 2021. The method was qualitative, with a retrospective approach. The population and sample are inpatient medical record documents in the fourth quarter of 2021 as many as 2,995 medical record documents and 5 officers. Used purposive sampling technique, with observation sheets and interviews. The results found were that 57,3% (1692 documents) didn’t comply with the procedure for returning medical record documents, and 42,7% (1263 documents) complied. Conclusion, the time for returning inpatient medical record documents for the fourth quarter of 2021 hasn’t been in accordance with existing procedures, because many medical record document returns exceed the 2x24 hour limit. The reason is disorganized administration of officers and there isn’t continuous evaluation to improve system for returning medical record documents with regulations. Suggestions monitoring of staff performance, as well as optimizing the use of computers to make it easier to find medical record documents that haven’t been returned.